2022
DOI: 10.1111/liv.15326
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 is overexpressed in advanced cirrhosis and predicts post‐liver transplant infectious complications

Abstract: Background & Aims: Patients with advanced cirrhosis often have immune dysfunction and are more susceptible to infections. Galectin-3 is a β-galactoside-binding lectin implicated in inflammation, immune regulation and liver fibrosis. We aim to investigate galectin-3 expression in advanced cirrhosis and its ability to predict post-transplant infectious complications. Methods:We collected sera and liver samples from 129 cirrhotic patients at the time of liver transplantation and from an external cohort of 37 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…Furthermore, Honsawek et al. did not compare BA patients to other CLD, and therefore it remained unknown if the elevation in serum Galectin‐3 was unique to BA, or was just a feature of chronic liver disease, as we have previously reported in adults 37 . In this study, we showed similar circulating levels of Galectin‐3 in late BA and other CLD, suggesting that elevation in circulating Galectin‐3 is indeed linked to the progression of end‐stage liver disease, rather than a unique feature of BA.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Honsawek et al. did not compare BA patients to other CLD, and therefore it remained unknown if the elevation in serum Galectin‐3 was unique to BA, or was just a feature of chronic liver disease, as we have previously reported in adults 37 . In this study, we showed similar circulating levels of Galectin‐3 in late BA and other CLD, suggesting that elevation in circulating Galectin‐3 is indeed linked to the progression of end‐stage liver disease, rather than a unique feature of BA.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, circulating Gal-3 has been found to be increased in dogs with noncardiac diseases such as severe dermatologic disease including neoplasia 66,67 and endocrine disease, 66 as well as in cirrhosis of the liver in human patients. 68 In experimental studies of animals with cardiac disease and in studies of humans without the above-listed diseases, concentrations of Gal-3 correlate well with the degree of myocardial fibrosis observed. We excluded patients with severe liver disease, those with any dermatologic abnormalities, and those with systemic hypertension or a diagnosis of neoplasia.…”
Section: Discussionmentioning
confidence: 92%
“…Estimates of right atrial volume may provide clinically relevant information regarding RV diastolic function, and measurement of right atrial area may have provided a more precise evaluation of the right atrial dimension compared to the linear variable used in our study. Additionally, circulating Gal‐3 has been found to be increased in dogs with noncardiac diseases such as severe dermatologic disease including neoplasia 66,67 and endocrine disease, 66 as well as in cirrhosis of the liver in human patients 68 . In experimental studies of animals with cardiac disease and in studies of humans without the above‐listed diseases, concentrations of Gal‐3 correlate well with the degree of myocardial fibrosis observed.…”
Section: Discussionmentioning
confidence: 98%
“…Patients were classified into compensated cirrhosis (CC), decompensated cirrhosis (DC), and ACLF, and the latter were further subdivided into ACLF grades 1, 2 and 3 (Figure 1 ). Diagnoses of CC and DC were based on the absence or presence of symptoms related to portal hypertension, including ascites, encephalopathy, or variceal bleeding, respectively, as previously described[ 14 ]. All CC patients received liver transplant because of hepatocarcinoma mainly due to hepatitis C virus (HCV) infection.…”
Section: Methodsmentioning
confidence: 99%